Analisis Kinerja Perusahaan Berbasis Balance Scorecard - Muhammad Ulin Nuha (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
Purpose - The purpose of this study was to analyze the company's performance based on the balanced scorecard at PT. Indofarma (Persero) Tbk. Design/methodology/approach - This research aims to analyze the company's performance using the Balanced Scorecard method, by measuring the company's performance not only from a financial perspective, but also measuring the company's performance from the perspective of the customer, internal business process perspective, and the learning and growth perspective. This research was conducted at the Indofarma PT. (Persero) Tbk, as PT Indofarma. (Persero) Tbk. has already implemented the Balanced Scorecard method. Findings - The results there are financial ratios that are less good, is the GPM, ROA, CR, and ROCE, because less than average – mean of the pharmaceutical industry in Indonesia, product availability, price cuts, and a realization of the products continue to decline. Implications - This study uses data from the Indonesian Stock Exchange website, idx.co.id